THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, TEACHER MOTIVATION, AND ORGANIZATIONAL CULTURE ON TEACHER PERFORMANCE IN PRIVATE VOCATIONAL SCHOOLS IN THE THIRD GROUP OF SOUTH TANGERANG CITY - Windaningsih, Windaningsih; Anwar, Saiful; Zubaidah, Siti (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
This study aims to analyze the influence of transformational leadership, teacher motivation, and organizational culture on teacher performance at Private Vocational Schools in Cluster Three of South Tangerang City, as well as to examine the role of organizational culture as a mediating variable. A quantitative approach with an associative design was employed, involving 153 teachers selected through simple random sampling. Data were collected using a Likert-scale questionnaire, tested for validity and reliability, and analyzed using multiple linear regression and path analysis. The findings indicate that transformational leadership, teacher motivation, and organizational culture have a significant positive direct effect on teacher performance (β = 0,216; 0,333; 0,250). Transformational leadership and teacher motivation also enhance organizational culture (β = 0.572; 0.255); however, the indirect effects through organizational culture are relatively small (β = 0.143; 0.064), making it a less effective mediator. Improving teacher performance is more effectively achieved through strengthening transformational leadership and teacher motivation directly, while organizational culture serves as a supporting factor.